Tempo e narrativa na Trilogia do adeus - Marcos, Eduardo da Rocha (2020)
This thesis aims to analyze the novels Caderno de um Ausente, Menina Escrevendo com Pai, and A Pele da Terra, which constitute the Trilogia do Adeus, by São Paulo writer João Anzanello Carrascoza. Based on the theoretical perspective of the philosopher Paul Ricoeur and the literary critic Gérard Genette, the research studies how the temporal and narrative categories are structurally articulated and what are the reflexes of this relationship for the construction of the works' meaning. The work also surveys which literary procedures are used in narrative writing. As a result, the study confirms the hypothesis that narrative is a possible way of inscribing itself in time, based on the transformation of lived experiences into narrative. Furthermore, it demonstrates, in the author's work, that temporality assumes the role of an articulating element in the cognitive elaboration of the trilogy.